Shame and guilt activations: Associations and sociodemographic differences among ploysubstance abusers - Abbasi, Najam ul Hasan; Iqbal, Mujahid; Yan, Yu; Mubarik, Sumaira; Nadeem, Muhammad; Turan, Mehmet Behzat; Younas, Romana (Frontiers in Psychiatry, 2022)
Objectives: Shame and guilt in polysubstance abusers are still understudied despite their significance in substance use disorder (SUD). The goal of the current study is to better understand how shame and guilt interact among polysubstance abusers who are receiving residential treatment. Method: The sample of 204 males with SUD was taken from five rehabilitation centers from two cities in Pakistan. For comparison, 215 age-matched healthy individuals were recruited (control). All participants reported their scores on the state shame and guilt scale (SSGS) and demographic form. A correlational study design was adopted. Results: The addiction group reported greater activations on SGSS shame and guilt scales (r = 0.79, p<0.001) as compared to healthy (control) individuals (r = 0.48, p<0.001). Further, multivariate analysis indicated that addicts with older age, unemployment, nuclear family system, higher level of education, and low-income, experience higher levels of shame and guilt. Multinomial logistic regression analysis revealed that addicted individuals in the age group 41-60 years (OR 5.2, 95%CI 2.4-6.8), unemployed (OR 4.4, 95%CI 3.2-4.7), nuclear family system (OR 5.9, 95%CI 4.5-6.4) and low monthly income group (OR 5.4, 95%CI 3.5-5.8) had a significantly high risk of shame and guilt than the control group. Conclusion: This finding of the current study shows a strong connection between shame and guilt activation, and SUD. These results reinforce that poly-substance users may benefit from therapeutic interventions to avoid a generalization of shame towards guilt. Reducing shame and guilt can be a priority of clinicians in treatment settings for adults with poly-drug problems.